Faktor-Faktor yang Berhubungan dengan Kejadian Hemorragic Postpartum di RSIA Adellia Graha Medika Lahat Tahun 2023 - Desandriani Aulia Fadyah; Siti Aisyah; Intan Sari; Wathan, Fika Minata (STIKes Budi Mulia Sriwijaya, 2025)
Postpartum hemorrhage is bleeding or loss of blood of 500 cc or more that occurs since the child is born. Bleeding can occur before, during, or even after the placenta is delivered. This study aims to determine the relationship between parity, pregnancy spacing and anemia with the incidence of Hemorrhagic Post Partum at RSIA Adellia Graha Medika Lahat Regency in 2023. The research method used in this study is quantitative research using an analytical survey with a cross-sectional approach with a population of 420 people, a sample of 81 using the random sampling method. Data analysis using the Chi Square statistical test with a p-value <α value = 0.05. The results of this study from 37 respondents with high parity 11 (30.6%) p.value = 0.013, from 39 respondents with risky birth spacing 12 (30.8%) p.value = 0.006, while from 37 respondents who experienced anemia 11 (29.7%) p.value = 0.018 experienced postpartum hemorrhagic events. Midwives are expected to provide counseling to pregnant women to maintain their health during pregnancy in order to prevent postpartum hemorrhagic events during childbirth.